Association of Hypertension with Raised Serum Homocysteine Levels - Ikram, Hasan; Jaffar, Syed Raza; Hayat, Asma; Kahttak, Mehnaz; Ellahi, Ayesha; Naeem, Afnan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the association of hypertension with raised serum homocysteine levels. Study Design: Comparative cross-sectional study. Place and Duration of Study: Army Medical College Rawalpindi in collaboration with Armed Forces Institute of Pathology and Military Hospital Rawalpindi, from Mar to May 2021. Methodology: Total study participants were four hundred in number. Two hundred patients with hypertension aged between 35-55 years were included in Group-1, whereas two hundred non-hypertensive patients with the closest possible age and sex matching were included in Group-2. Strict adherence to inclusion and exclusion criteria was ensured. Results: The mean age of patients with hypertension (Group 1) was 42.60 ± 9.95 years, and without hypertension, i.e., healthy participants (Group 2), was 42.26 ± 10.03 years. Systolic BP was 157.92 ± 8.07 mmHg among Group 1 (hypertensive subjects) and 114.60 ± 4.58 mmHg among Group 2 (healthy participants). Mean diastolic blood pressure in patients with hypertension (Group 1) was 104.95 ± 5.87 mmHg, whereas it was 74.20 ± 4.74 mmHg among non-hypertensive healthy participants (Group 2). Mean serum homocysteine level was significantly correlated with hypertension (p-value <0.001, r=0.804 for systolic and p-value <0.001, r=0.792 for diastolic blood pressure) and was higher in Group 1(20.64 ± 4.40 µmol/L) than that of healthy Group 2(9.48 ± 2.38 µmol/L). Conclusion: Our study concludes that serum homocysteine had a significant positive correlation with hypertension and can be used as an early marker for hypertension assessment in addition to regular blood pressure measurements.